Insights on the role of cryoprotectants in enhancing the properties of bioinks required for cryobioprinting of biological constructs - Harshavardhan Budharaju; Dhakshinamoorthy Sundaramurthi; Swaminathan Sethuraman (Journal of Materials Science: Materials in Medicine)
Abstract Preservation and long-term storage of readily available cell-laden tissue-engineered products are major challenges in expanding their applications in healthcare. In recent years, there has been increasing interest in the development of off-the-shelf tissue-engineered products using the cryobioprinting approach. Here, bioinks are incorporated with cryoprotective agents (CPAs) to allow the fabrication of cryopreservable tissue constructs. Although this method has shown potential in the fabrication of cryopreservable tissue-engineered products, the impact of the CPAs on the viscoelastic behavior and printability of the bioinks at cryo conditions remains unexplored. In this study, we have evaluated the influence of CPAs such as glycerol and dimethyl sulfoxide (DMSO) on the rheological properties of pre-crosslinked alginate bioinks for cryoprinting applications. DMSO-incorporated bioinks showed a reduction in viscosity and yield stress, while the addition of glycerol improved both the properties due to interactions with the calcium chloride used for pre-crosslinking. Further, tube inversion and printability experiments were performed to identify suitable concentrations and cryobioprinting conditions for bioinks containing CPAs & pre-crosslinked with CaCl2. Finally, based on the printability analysis & cell recovery results, 10% glycerol was used for cryobioprinting and preservation of cell-laden constructs at −80 °C and the viability of cells within the printed structures were evaluated after recovery. Cell viability results indicate that the addition of 10% glycerol to the pre-crosslinked bioink significantly improved cell viability compared to bioinks without CPAs, confirming the suitability of the developed bioink combination to fabricate tissue constructs for on-demand applications. Graphical abstract Effect of cryoprotectants on the viscoelastic behavior of bioinks and cell recovery in cryobioprinted tissue constructs.